Variation in chemical composition and physical characteristics of cereal grains from different genotypes. Issue 2 (3rd March 2016) - Rodehutscord, Markus; Rückert, Christine; Maurer, Hans Peter; Schenkel, Hans; Schipprack, Wolfgang; Bach Knudsen, Knud Erik; Schollenberger, Margit; Laux, Meike; Eklund, Meike; Siegert, Wolfgang; Mosenthin, Rainer
ABSTRACT: Genotypes of cereal grains, including winter barley ( n  = 21), maize ( n  = 27), oats ( n  = 14), winter rye ( n  = 22), winter triticale ( n  = 21) and winter wheat ( n  = 29), were assayed for their chemical composition and physical characteristics as part of the collaborative research project referred to as GrainUp. Genotypes of one grain species were grown on the same site, except maize. In general, concentrations of proximate nutrients were not largely different from feed tables. The coefficient of variation (CV) for the ether extract concentration of maize was high because the data pool comprised speciality maize bred for its high oil content. A subset of 8 barley, 20 rye, 20 triticale and 20 wheat samples was analysed to differ significantly in several carbohydrate fractions. Gross energy concentration of cereal grains could be predicted from proximate nutrient concentration with good accuracy. The mean lysine concentration of protein was the highest in oats (4.2 g/16 g N) and the lowest in wheat (2.7 g/16 g N). Significant differences were also detected in the concentrations of macro elements as well as iron, manganese, zinc and copper. Concentrations of arsenic, cadmium and lead were below the limit of detection. The concentration of lower inositol phosphates was low, but some inositol pentaphosphates were detected in all grains. In barley, relatively high inositol tetraphosphate concentration also was found. Intrinsic phytase activity was the highest in rye, followed by triticale, wheat, barley and maize, and it was not detectable in oats. Substantial differences were seen in the thousand seed weight, test weight, falling number and extract viscoelasticity characteristics. The study is a comprehensive overview of the composition of different cereal grain genotypes when grown on the same location. The relevance of the variation in composition for digestibility in different animal species will be subject of other communications.